PKM PELATIHAN PENILAIAN STATUS GIZI SISWA BAGI GURU-GURU SD NEGERI 13 BIRU KECAMATAN TANETE RIATTANG KABUPATEN BONE - Muliadi Muliadi; Sitti Jauhar; Sudarto Sudarto (Bajang Institute, 2023)
This PKM service aims to help partners overcome nutritional status problems for elementary school students at SD Negeri 13 Biru, Tanete Riattang sub-district, Bone district. There are several obstacles faced by elementary school teachers on the nutritional status of students, including the lack of understanding and concern of teachers to assess the nutritional status of students, lack of skill of teachers in measuring and determining nutritional status based on anthropometry. This activity provides teachers with understanding and skills about assessing nutritional status for students. This activity is useful for all students to know their nutritional status, for teachers it is useful in indicators of student health. This PKM activity stage is carried out in three stages, namely; The first stage provides knowledge/understanding of the concept of balanced nutrition, the goals and benefits of nutrition for humans and more specifically for elementary school students (the period of growth and development). Then the second activity stage is carried out with the mentoring method, namely carrying out the practice of measuring and assessing status based on Anthropometry of elementary school students, the third stage is demonstrating and evaluating training participants in implementing the nutritional status of elementary school students.